Post-COVID-19 anxietydisorder: A literature review (Research, Society and Development, 2024)
Introduction: Anxiety Disorder is a recurrent condition that impairs the psychosocial functioning of sufferers. Its symptoms are negative thoughts with which to come associated with receiving risky situations, with tension or discomfort arising from the anticipation of danger, of something unknown or strange. Anxiety Disorder was even more prevalent in the context of the pandemic caused by the SARS-CoV-2 virus, since the COVID-19 infection may be able to develop the disease crises. Methodology: An integrative review was carried out in the databases indexed in Google Scholar and the Virtual Health Library (BVS), using as inclusion criteria articles published from 2009 to 2022, in English and Portuguese, and as criteria for exclusion, duplicate articles and those unrelated to the topic Results and discussion: There were several factors associated with the worsening or development of Panic Disord er due to COVID-19 infection, whose clinical importance is linked to the profile of the patient treated. The main risk factors for this development studied were: Younger age of the patient, need for hospitalization in the ward and Intensive Care Unit associated with family isolation, severity of symptoms, lack of knowledge of the disease, and abandonment of treatment for an anxiety disorder already diagnosed . Conclusion: The worsening or increase in the frequency of anxiety disorder crises occurred significantly more in two moments: during and after the period of active infection by COVID-19, having risk factors that have not yet been well elucidated by the current literature.